2022
DOI: 10.1109/access.2021.3139684
|View full text |Cite
|
Sign up to set email alerts
|

Non-Decimated Wavelet Based Multi-Band Ear Recognition Using Principal Component Analysis

Abstract: Principal Component Analysis (PCA) has been successfully applied to many applications, including ear recognition. This paper presents a 2D Wavelet based Multi-Band Principal Component Analysis (2D-WMBPCA) ear recognition method, inspired by PCA based techniques for multispectral and hyperspectral images. The proposed 2D-WMBPCA method performs a 2D non-decimated wavelet transform on the input image, dividing it into its wavelet subbands. Each resulting subband is then divided into a number of frames based on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…• MATTHEW et al [18] presented a novel method for ear recognition, called the 2D Wavelet based Multi-Band PCA (2D-WMBPCA) technique. Inspired by PCA-based methods for multispectral and hyperspectral images, the proposed method involves a 2D non-decimated wavelet transform applied to the input image, resulting in wavelet subbands.…”
Section: Handcrafted Featuresmentioning
confidence: 99%
“…• MATTHEW et al [18] presented a novel method for ear recognition, called the 2D Wavelet based Multi-Band PCA (2D-WMBPCA) technique. Inspired by PCA-based methods for multispectral and hyperspectral images, the proposed method involves a 2D non-decimated wavelet transform applied to the input image, resulting in wavelet subbands.…”
Section: Handcrafted Featuresmentioning
confidence: 99%
“…Researchers have explored this topic extensively over the last two decades, investigating techniques for extracting features from ear images and their subsequent comparison [10,28]. Successful feature extraction techniques in ear recognition and other biometrics include Principal Component Analysis-(PCA) [29][30][31][32]37], wavelet-based [5,13,18,25], Support Vector Machine (SVM) [4,26,27] and neural network-based and other [1,2,7,9,11,15,22,24,27,33,39,40] methods. Amongst these techniques, PCA has been used for both feature extraction in the form of eigenvectors and dimensionality reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the multi-band image processing for ear recognition on non-decimated wavelet subbands of ear images utilizing Principal Component Analysis (PCA) shows the effectiveness of multi-band image processing in recognition. In [18], the authors showed that the intersection of the number of feature graphs and the Eigenvector energy defines the optimum number of bands for recognition, where increasing the number of multi-band images changes the distribution of the energy across image Eigenvectors, and consolidates most of the image Eigenvectors' energy into a smaller number of Eigenvectors. The result of this was an increased accuracy in recognition.…”
Section: Introductionmentioning
confidence: 99%